COVID-19 and ‘immune boosting’ on the internet: a content analysis of Google search results - Rachul, Christen (BMJ Open, 2020)
OBJECTIVE: The spread of misinformation has accompanied the coronavirus pandemic, including topics such as immune boosting to prevent COVID-19. This study explores how immune boosting is portrayed on the internet during the COVID-19 pandemic. DESIGN: Content analysis. METHODS: We compiled a dataset of 227 webpages from Google searches in Canada and the USA using the phrase ‘boost immunity’ AND ‘coronavirus’ on 1 April 2020. We coded webpages for typology and portrayal of immune boosting and supplements. We recorded mentions of microbiome, whether the webpage was selling or advertising an immune boosting product or service, and suggested strategies for boosting immunity. RESULTS: No significant differences were found between webpages that appeared in the searches in Canada and the USA. The most common types of webpages were from news (40.5%) and commercial (24.7%) websites. The concept of immune boosting was portrayed as beneficial for avoiding COVID-19 in 85.5% of webpages and supplements were portrayed as beneficial in 40% of the webpages, but commercial sites were more likely to have these portrayals. The top immune boosting strategies were vitamin C (34.8%), diet (34.4%), sleep (34.4%), exercise (30.8%) and zinc (26.9%). Less than 10% of the webpages provide any critique of the concept of immune boosting. CONCLUSIONS: Pairing evidence-based advice for maintaining one’s health (eg, healthy diet, exercise, sleep) with the phrase immune boosting and strategies lacking in evidence may inadvertently help to legitimise the concept, making it a powerful marketing tool. Results demonstrate how the spread of misinformation is complex and often more subtle than blatant fraudulent claims.